Effect on the size of optic nerve sheath diameter in patients undergoing surgeries under spinal anaesthesia versus peripheral nerve blocks – A randomised controlled study - Sangineni Kalyani Surya Dhana Lakshmi; A Bhargav Ram; CH Rama Krishna Prasad; Sandeep Garre; Anish Waghray (Indian Journal of Anaesthesia)
Background and Aims: Post-dural puncture headache is a complication of spinal anaesthesia, theorised to be triggered by a lowering in intracranial pressure due to the cerebrospinal fluid leak through the dural puncture. Our objective was to evaluate whether there is a decrease in optic nerve sheath diameter (ONSD) with a reduction in intracranial pressure after spinal anaesthesia. Methods: Patients were randomised by a computer-generated randomisation table to receive spinal anaesthesia (Group S) or peripheral nerve block (Group P) after assessing their eligibility for the anaesthesia procedure as per the protocol. The ONSD was measured in the preoperative period and again at 4 h and 24 h after the anaesthetic, both in the supine and sitting positions, along with haemodynamic parameters. Continuous variables such as age, height, weight, mean arterial pressures, and ONSD were expressed as mean [standard deviation (SD)] [95% confidence interval (CI)] and compared using the student’s t-test. Repeated measure ANOVA and Bonferroni were used to compare intra-group parameters. Results: The mean decrease in the ONSD from a baseline mean of 3.95 (SD: 0.17) (95%CI: 3.87, 4.02) to 3.89 (SD: 0.26) (95%CI: 3.78, 4.007) mm at 4 h and 3.94 (SD: 0.12) (95%CI: 3.89, 4.0) mm at 24 h after spinal anaesthesia was statistically significant. The changes in the ONSD measurements in Group P were not statistically significant. Headache was not reported at 24 h or in the follow-up at postoperative day 5. Conclusion: Measurement of ONSD is an easy, economical method for identifying decreased intracranial pressure after spinal anaesthesia. Further research could identify cut-off values to prognosticate PDPH in high-risk individuals.